THE ROLE OF RULES OF COMPOSITION IN ENHANCING ARCHITECTURAL VISUAL LITERACY (RATE OF ARCHITECTURAL VISUAL LITERACY IN ERBIL) - MUSLAT, HAMEEDA I.; KHAYAT, MAHMOOD AHMED (Journal of Duhok University, 2023)
Architecture can be regarded as a system or a language that relies heavily on visual communication to recognize, perceive, and interpret the built environment. This visual language goes beyond the traditional literacy skills of reading and writing, yet it demands visual principles inherent in architectural compositions. Although language and architecture differ in their forms, they converge on common ground of communication. This study aims to determine the rate of literate audiences in architecture, which presents challenges due to the complex and dynamic nature of literacy and the diverse design strategies of architecture. By drawing inspiration from the influential work of Francis D. Ching’s book Architecture: Form, Space, And Order, this research evaluates how effectively the field of architecture, and its practitioners, engage and communicate with audiences through visual means. This study illuminates the rate of the literate audience by providing a framework applied to selected case studies in Erbil city featuring diverse architectural compositions. The expected results are, first, providing guidelines of principles derived from Ching’s work to enrich architectural practices. Secondly, exploring effective visual communication through enhanced visual literacy utilizing these principles. By understanding the audience's ability to read architectural language, this research lays the foundation for future design practices, empowering architects to create communicative built environments.